2006
DOI: 10.1093/jnci/djj373
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Eradicating Therapy With Doxycycline in Ocular Adnexal MALT Lymphoma: A Multicenter Prospective Trial

Abstract: Doxycycline is a fast, safe, and active therapy for Cp DNA-positive OAL that was effective even in patients with multiple failures involving previously irradiated areas or regional lymphadenopathies. The responses observed in PCR-negative OAL may suggest a need for development of more sensitive methods for Cp detection and investigation of the potential role of other doxycycline-sensitive bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
147
1
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(158 citation statements)
references
References 32 publications
5
147
1
5
Order By: Relevance
“…Micro-organisms have been implicated in the pathogenesis of MALT lymphoma arising from some locations, 16 with successful treatment by using antibiotics, most notably doxycycline for orbital MALT lymphomas. [17][18][19] However, the results are still premature to consider it as a primary modality of therapy because durable remission has only been documented in 48% in a cohort of 27 patients treated 19 and that a uniformly high response rate has not been reported by other investigators. 20 However, it is a nonmorbid treatment, and therefore an attractive initial treatment approach and can spare or delay the use of cytotoxic therapy such as RT.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-organisms have been implicated in the pathogenesis of MALT lymphoma arising from some locations, 16 with successful treatment by using antibiotics, most notably doxycycline for orbital MALT lymphomas. [17][18][19] However, the results are still premature to consider it as a primary modality of therapy because durable remission has only been documented in 48% in a cohort of 27 patients treated 19 and that a uniformly high response rate has not been reported by other investigators. 20 However, it is a nonmorbid treatment, and therefore an attractive initial treatment approach and can spare or delay the use of cytotoxic therapy such as RT.…”
Section: Discussionmentioning
confidence: 99%
“…While gastric MALT lymphomas are invariably associated with Helicobacter species, pulmonary MALT lymphoma, similarly to other non-gastric MALT lymphomas, might be associated with several infectious agents. A recent study from Italy showed that 6 of the 13 C. psittaci negative ocular MALT lymphomas also responded to antibiotic treatment, suggesting the presence of other bacteria (Ferreri et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…119 Nearly 80% of early stage H. pylori-associated gastric MZBCLs, but also a proportion of cutaneous and ocular adnexal MZBCLs is curable by bacterial eradication alone. 62,164,165 Similarly, IFNα-2b treatment can cause regression of HCV-associated MZBCL. 166,167 In vitro culture experiments with gastric MZBCL cells have revealed that the tumor B cells do not respond to H. pylori directly, but instead depend for their survival on stimuli provided by intra-tumoral, H. pylori-specific T cells.…”
Section: Bcr Specificity Of Marginal Zone B-cell Lymphomasmentioning
confidence: 99%